NAT10-mediated ac4C modification promotes stemness and chemoresistance of colon cancer by stabilizing NANOGP8 - Li-ping Gao; Ting-dong Li; Su-zhen Yang; Hui-min Ma; Xiang Wang; De-kui Zhang (Heliyon, 2024)
Background: Colon cancer (CC) stem cells can self-renew as well as expand, thereby promoting tumor progression and conferring resistance to chemotherapeutic agents. The acetyltransferase NAT10 mediates N4-acetylcytidine (ac4C) modification, which in turn drives tumorigenesis, metastasis, stemness properties maintenance, and cell fate decisions. Nonetheless, the specific involvement of ac4C modification mediated by NAT10 in regulating stemness and chemosensitivity in CC remains undetermined. Methods: The levels of NAT10 in normal colon and chemoresistant CC tissues were determined utilizing quantitative real-time polymerase chain reaction alongside immunohistochemistry. Assessing cancer cell stemness and chemosensitivity was conducted by various methods including spheroid and colony formation, western blotting, and flow cytometry. RNA-Seq was used to identify target genes, and RNA immunoprecipitation analysis was used to explore the potential mechanisms. Results: We observed NAT10 overexpression and increased ac4C modification levels in chemoresistant CC tissues. The in vivo and in vitro analysis findings suggested that NAT10 promoted CC cell stemness while suppressing their chemosensitivity. Conversely, Remodelin, a NAT10-specific inhibitor, enhanced CC cell chemosensitivity. Mechanistically, NAT10 increased the level of NANOGP8 ac4C modification and promoted NANOGP8 mRNA stability. Conclusions: NAT10 promotes the maintenance of stemness and chemoresistance in CC cells by augmenting the mRNA stability of NANOGP8. The inhibition of NAT10 via Remodelin improves chemotherapeutic efficacy and impedes CC progression.